2021
DOI: 10.1158/0008-5472.can-20-2041
|View full text |Cite
|
Sign up to set email alerts
|

The miR–181a–SFRP4 Axis Regulates Wnt Activation to Drive Stemness and Platinum Resistance in Ovarian Cancer

Abstract: Wnt signaling is a major driver of stemness and chemoresistance in ovarian cancer, yet the genetic drivers that stimulate its expression remain largely unknown. Unlike other cancers, mutations in the Wnt pathway are not reported in high-grade serous ovarian cancer (HGSOC). Hence, a key challenge that must be addressed to develop effective targeted therapies is to identify nonmutational drivers of Wnt activation. Using an miRNA sensor-based approach, we have identified miR-181a as a novel driver of Wnt/β-cateni… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…miR-181a has been shown to target PTEN , a gene responsible for apoptosis regulation [ 25 ]. It has also been shown to play a role in the regulation of the Wnt, STAT3 and RAS/MAPK pathways, which have been implicated in leukemia development [ 26 , 27 , 28 ]. miR-181a has been shown to increase cell sensitivity to chemotherapeutic drugs by targeting several antiapoptotic genes [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…miR-181a has been shown to target PTEN , a gene responsible for apoptosis regulation [ 25 ]. It has also been shown to play a role in the regulation of the Wnt, STAT3 and RAS/MAPK pathways, which have been implicated in leukemia development [ 26 , 27 , 28 ]. miR-181a has been shown to increase cell sensitivity to chemotherapeutic drugs by targeting several antiapoptotic genes [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In cancer such as pancreatic cancer, lung adenocarcinomas, colorectal cancer, and liver cancer, the small subpopulation of cancer cells expressing high Wnt/β-catenin signaling showed CSCs phenotype and were resistant to drug. The inhibition of Wnt signaling in these cells suppressed the stem cells phenotype, thereby affecting the chemoresistance (Taelman et al, 2010;Ilmer et al, 2015;Belur Nagaraj et al, 2021).…”
Section: Enrichment/induction Of Cancer Stem Cell Like Phenotypementioning
confidence: 99%
“…Multiple ncRNAs, including miRNAs and lncRNAs, are increasingly implicated in the treatment resistance in OC ( 194 , 195 ). Therefore, targeting tumor-specific miRNAs and lncRNAs is expected to overcome drug resistance of OC.…”
Section: Therapeutic Targeting Of the Oc Epigenomementioning
confidence: 99%
“…Recently, miRNAs have received increasing attention as biomarkers and therapeutic targets for OC. For instance, Belur Nagaraj and colleagues found that miR-181a is an activator of Wnt/β-catenin signaling, driving stemness and chemotherapy resistance in high-grade serous ovarian cancer (HGSOC), thus being a potential target for treating recurrent OC ( 194 ). Using next-generation sequencing (NGS) techniques, Au Yeung et al.…”
Section: Therapeutic Targeting Of the Oc Epigenomementioning
confidence: 99%